Does middle income trap exist?: Evidence from emerging economies: E7 countries for 1969-2015 - (:unkn) unknown (Universidade de Santiago de Compostela, 2018)
The E7 countries (China, India, Brazil, Russia, Mexico, Indonesia and Turkey) that have been growing fast since 1990s have been under the middle income country category according to the income category classification of the World Bank for a long period of time. Researchers have been interested especially in emerging economies that have not been able to move up from the middle income category to the high income category and this has led to the initiation of what’s called the ‘middle income trap’ (MIT) discussions in literature. The MIT is generally defined as the countries under the middle income category failing to move up to the high income category. Therefore, the purpose of this study is to identify the presence of MIT in E7 countries that hold an important position in global economy. The unit root tests were used in the empirical phase of the study. This study’s difference from other studies is the fact that both the time series and the panel data unit root tests were used both in linear and nonlinear forms, thus preventing the misleading results created by choosing the wrong model specification. The USA was taken as the reference country in the study and the GNI per capita according to the Atlas method (current US$) data of the World Bank was used for the E7 countries for the period 1969-2015. To achieve consistency in the analysis results, Russia was not included in the model as there were no data available for the same period for Russia given the fact that the same timeframe should be taken as the basis for all countries. The empirical analysis showed that the E7 countries do not fall into the MIT. © 2018, Universidade de Santiago de Compostela. All rights reserved.
Keywords: Emerging 7 Countries (E7); Middle-income countries; Middle-income trap; Unit root tests